Is idiosyncratic risk ignored in asset pricing: Sri Lankan evidence? - Moinak Maiti (Future Business Journal, 2019)
The present study focused on one of the important South Asian nations-Sri Lanka-to examine the role of idiosyncratic volatility in asset prices. A four-factor model with idiosyncratic volatility was designed for capturing the market, size, value and idiosyncratic risk yields better than Fama and French's (J Financ Econ 33:3-56, 1993) three-factor model and performance of the model. Fama-MacBeth's cross-sectional regression, residual graphs and GRS test all confirm the superiority of four-factor model over 2 three-factor models. For all MC- and IVOL-based portfolios, idiosyncratic volatility is negatively related to the expected returns and positively related for all PB-based portfolios. Finally, study findings confirm that there is a high importance for idiosyncratic volatility risk factor while considering investment decision in Colombo stock exchange. Hence, investor should compensate for holding such risk factors in the portfolio.
Keywords: G12; 650; Asset pricing; Idiosyncratic risk; Factor models; Fama-MacBeth' cross-sectional regression; Risk